THE EFFECT OF MAGNESIUM SULFATE NEBULIZATION IN ACUTE EXACERBATION OF ASTHMA - MAJEED , A; SAEED, M; SUKRIYA, B; ULLAH, K; TESNEEM, SS; JABEEN, R (Biological and Clinical Sciences Research Journal, 2024)
Acute exacerbations of asthma are a significant public health challenge, particularly in resource-limited settings. Nebulized magnesium sulfate has shown potential as an adjunctive therapy in managing asthma exacerbations, but its effectiveness and safety in the Pakistani population remain underexplored. Objective: To evaluate the effectiveness and safety of nebulized magnesium sulfate in managing acute asthma exacerbations in a tertiary care hospital in Pakistan. Methods: A descriptive cross-sectional study was conducted among 200 participants with acute asthma exacerbations. Nebulized magnesium sulfate was administered as part of standard or adjunctive therapy. Symptom severity, including shortness of breath, wheezing, and chest tightness, was assessed before and after treatment. Data were analyzed using SPSS version 26, with descriptive statistics summarizing findings. Results: Significant symptom improvement was observed following treatment. The proportion of patients reporting mild shortness of breath increased from 0% to 40.5%, and mild wheezing from 0% to 62.0%. No adverse effects were reported, and 58.0% of participants rated the treatment as somewhat effective. Satisfaction levels were also high, with 58.5% somewhat satisfied and 21.0% very satisfied with the treatment. Conclusion: Nebulized magnesium sulfate is an effective and safe adjunctive therapy for acute asthma exacerbations. Its inclusion in treatment protocols can improve patient outcomes, particularly in resource-constrained healthcare settings. Further studies are warranted to develop standardized guidelines for its use.